Annotated bird sighting list for Spring 1986 compiled by Ray Cummins - Cummins, Raymond L.et al (1986)
An annotated list of birds sighted by Ray Cummins. Includes report form for selected species in Spring indicating early, peak and late sightings for selected species. This item was used as supporting documentation for the Iowa Ornithologists Union Quarterly field report of Spring 1986. Epson - sheet feed